Dear daddy - Dupasquier, Philippe (England : Longman, 1998)
The top portion of each double page spread shows Sophie's father on a long sea voyage, while the bottom portion shows her activities at home as she is decribing them in a series of letters.
K-3.
Keywords: Family life -- Fiction; Seafaring life -- Fiction; Father and daughters -- Fiction